1979
DOI: 10.1111/j.1432-1033.1979.tb02057.x
|View full text |Cite
|
Sign up to set email alerts
|

Active-Site-Specific Reconstituted Cobalt(II) Horse-Liver Alcohol Dehydrogenase. Changes of the Spectra of the Substrate trans-4-(N,N-Dimethylamino)-cinnamaldehyde and of the Catalytic Cobalt Ion upon Ternary Complex Formation with NADH and 1,4,5,6-Tetrahydronkotinamide-Adenine Dinucleotide

Abstract: Horse liver alcohol dehydrogenase (EC 1 .l. 1. l), specifically reconstituted with cobaltous ions in the catalytic metal-binding sites, forms ternary complexes with the chromophoric substrate trans-4-(N,N-dimethylamino)-cinnamaldehyde and NADH or 1,4,5,6-tetrahydronicotinamide-adenine dinucleotide (H2NADH), in close analogy to the native zinc enzyme [Dunn, M. F. and Hutchison, J. S. (1973) Biochemistry, 12, 4882-48921. Control experiments with enzyme depleted of metal in the catalytic sites demonstrate that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 12 publications
2
24
1
Order By: Relevance
“…When the catalytic zinc of TBADH was substituted by such metals as cobalt or cadmium, the rates of the enzymatic reactions were 1.3 and 0.02 of those for the zinc enzyme. Similar results have been reported for HLADH (Dunn & Hutchison, 1973;Dietrich et al, 1979;Moms et al, 1980;Dunn et al, 1982). The results correlated with the expected order of Lewis acidity (for a tetrahedral ligand field) Co 2 Zn >> Cd (Dunn et al, 1982).…”
Section: Metal Substitution In Tbadhsupporting
confidence: 88%
“…When the catalytic zinc of TBADH was substituted by such metals as cobalt or cadmium, the rates of the enzymatic reactions were 1.3 and 0.02 of those for the zinc enzyme. Similar results have been reported for HLADH (Dunn & Hutchison, 1973;Dietrich et al, 1979;Moms et al, 1980;Dunn et al, 1982). The results correlated with the expected order of Lewis acidity (for a tetrahedral ligand field) Co 2 Zn >> Cd (Dunn et al, 1982).…”
Section: Metal Substitution In Tbadhsupporting
confidence: 88%
“…45 Spectra showed that trans -4-( N , N -dimethylamino)cinnamaldehyde binds to the Co(II) in the complex with 1,4,5,6-tetrahydronicotinamide adenine dinucleotide. 81,82 The NMR study was extended to ternary complexes with NADH and dimethyl sulfoxide or NAD + and 2,2,2-trifluoroethanol, and again it was concluded that the oxygens of the ligands were not directly ligated to the metal. 83 However, other studies concluded that the paramagnetic effects of Co(II) on the relaxation of water or alcohol protons were too small to give reliable determinations of the distance of the protons from the metal.…”
Section: Discussionmentioning
confidence: 99%
“…However, a low-resolution X-ray crystallography study suggested that substrates and inhibitors bind directly to the zinc in enzyme–coenzyme complexes that resemble Michaelis complexes . Spectra showed that trans -4-( N , N -dimethylamino)­cinnamaldehyde binds to the Co­(II) in the complex with 1,4,5,6-tetrahydronicotinamide adenine dinucleotide. , The NMR study was extended to ternary complexes with NADH and dimethyl sulfoxide or NAD + and 2,2,2-trifluoroethanol, and again it was concluded that the oxygens of the ligands were not directly ligated to the metal . However, other studies concluded that the paramagnetic effects of Co­(II) on the relaxation of water or alcohol protons were too small to give reliable determinations of the distance of the protons from the metal. , After higher-resolution X-ray studies clearly showed that the oxygens of the ligands are directly ligated to a tetracoordinated zinc and that there is no water near the zinc, we proposed that the oxygen of the substrate is bound to the zinc, and the proton is transferred to or from the substrate through a hydrogen-bonded system, including the hydroxyl group of Ser-48 and the imidazole group of His-51 …”
Section: Discussionmentioning
confidence: 99%
“…X-ray crystallography of the metal-substituted cadmium and cobalt enzymes has shown that the distorted tetrahedral coordination geometry is retained [22,23]. Spectroscopic studies with Co(II)-and Cd(II)-substituted enzymes [24][25][26] have suggested geometrical changes at the catalytic metal site upon coenzyme binding similar to those observed with the zinc enzyme. The structure of the copper-substituted complex of HLADH with DMSO has been determined to 2.10 A H [27].…”
Section: Introductionmentioning
confidence: 96%